Prevalence of Protein and Pre-Workout Supplement Use among High School Football Players and Potential Product Contamination. (July 2021) - Shoshan, Tal; Post, Eric
The purpose was to determine the prevalence of protein and pre-workout supplement usage in high school football players and how many products contained banned substances or dangerous ingredients. A national sample of 102 high school football players was recruited via Qualtrics Research Panels to complete a cross-sectional online questionnaire. Data were summarized as means with standard deviations (SDs) and frequencies with proportions (%). A majority (59.8%) of high school football players reported currently using a protein supplement. Just under one-third (29.4%) reported currently using pre-workout supplements. Five participants reported using a pre-workout product that contained a known NCAA banned substance. Many of the products used contain banned, regulated elsewhere, or unknown substances. Secondary school ATs must educate athletes regarding the use of nutritional supplements and the potential dangers of ingesting banned or unknown substances.